The Effect of Compensation on Employee Work Productivity (Case Study at Bukit Alamanda Resto & Resort) - Risan Sugiayasin; Ai Siti Hawa (International Journal of Economics (IJEC), 2022)
This research has a background where work productivity at Bukit Alamanda Resto & Resort is still not optimal in carrying out its duties, principals and functions as an employee. based on the pre-survey the cause of the not optimal work productivity of employees due to not optimal compensation given. The purpose of this study was to determine the effect of compensation on work productivity at work at Bukit Alamanda Resto & Resort. The population in this study were 46 people. Given that the population is less than 100 people, in this study the authors will use the saturated sample method, which means that all populations are used as respondents in the study. This type of quantitative research uses descriptive and associative methods. Analysis of the data used in this study include: table analysis, correlation test, test the coefficient of determination and test the hypothesis. Based on the results of statistical analysis calculations using the correlation test between compensation on work productivity, a correlation result of 0.358 was obtained, the correlation coefficient was at intervals of 0.20-0.399 so it can be interpreted that the relationship between compensation on employee work productivity at Bukit Alamanda Resto and Resort has a correlation currently. For the calculation of the determination test, the result is 0.128 or 12.8%. This shows that employee work productivity is influenced by compensation and the remaining 87.2% is influenced by other factors not examined.